Factors Influencing Female Managerial Performance: A Pilot Study for Model Validation - Pálmai, László; Kőmüves, Zsolt; Végvári, Bence; Szécsi, Gabriella (Emerging Science Journal, 2025)
This pilot study examines factors influencing the performance of female managers by testing a structural model that integrates psychosocial and organizational dimensions. The model includes organizational culture, managerial power, discrimination, prejudice, insecurity, and family roles. Data were collected through a survey of 179 female managers in Hungary. As the sample is geographically limited, the findings should be interpreted with caution. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyze the relationships among variables. Results indicate that a supportive organizational culture enhances perceptions of managerial power, which positively influences leadership performance. Conversely, experiences of discrimination reinforce prejudices, while family-related obligations heighten perceived bias toward women in leadership. Insecurity was also found to negatively impact managerial performance. The model showed strong internal reliability and acceptable discriminant validity, supporting its use in further research. This study offers novel insights by jointly examining individual, organizational, and societal barriers within a unified framework. Beyond its theoretical contribution, the findings provide practical guidance for organizations and policymakers aiming to foster inclusive leadership environments and promote gender equity in the workplace.